Tranexamic acid decreases the magnitude of platelet dysfunction in aspirin-free patients undergoing cardiac surgery with cardiopulmonary bypass: a pilot study. Issue 8 (December 2016) - Van Aelbrouck, Caroline; Jorquera-Vasquez, Sebastian; Beukinga, Ingrid; Pradier, Olivier; Ickx, Brigitte; Barvais, Luc; Van Obbergh, Luc; Faraoni, David
Abstract : This study sought to compare the effect of tranexamic acid (TXA) administration on cardiopulmonary bypass-induced platelet dysfunction in patients who received preoperative aspirin or not. We performed a prospective, randomized, double-blind pilot study, including patients undergoing elective cardiac surgery with cardiopulmonary bypass (CPB). Patients without aspirin interruption were enrolled in the 'group ASPIRIN' ( n = 18) and those who had never been treated with aspirin were included in the 'group NO ASPIRIN' ( n = 10). Patients were then randomized to receive either TXA or the same infusion of normal saline. Multiple electrode aggregometry was used to assess platelet function at the different time points throughout the surgery: baseline, post-TXA loading dose, aortic unclamping (End CPB), and 5 min after protamine (Protamine). Compared to those included in the group NO ASPIRIN, patients included in the group ASPIRIN presented a decreased baseline platelet function measured by ASP test ( P < 0.01) and collagen test ( P < 0.01). In the group NO ASPIRIN, treatment group (TXA vs. placebo) significantly influenced the results for ADP test ( P < 0.01), thrombin receptor-activating peptide test ( P = 0.01), and ASP test ( P = 0.01). We observed that TXA improved platelet function, as measured using multiple electrode aggregometry on ADP test, thrombin receptor-activating peptide test, and ASP test, at the end of CPB ( P < 0.05). TXA might decrease the magnitude of platelet dysfunction in aspirin-free patients undergoing cardiac surgery. Further studies are needed to confirm these results and assess a potential relationship with clinical endpoints.